Different Mechanisms Preserve Translation of Programmed Cell Death 8 (PDCD8) and JunB in Virus-Infected Endothelial Cells - Jiang, Huimiao (2012)
OBJECTIVE: Translation initiation of eukaryotic mRNAs typically occurs by cap-dependent ribosome scanning mechanism. However, certain mRNAs are translated by ribosome assembly at internal ribosome entry sites (IRES). Whether IRES-mediated translation occurs in stressed primary human endothelial cells (EC) is unknown. METHODS AND RESULTS: We performed microarray analysis of polyribosomal mRNA from EC to identify IRES-containing mRNAs. Cap-dependent translation was disabled by poliovirus (PV) infection and confirmed by loss of polysome peaks, detection of eIF4G cleavage, and decreased protein synthesis. 87.4% of mRNAs were dissociated from polysomes in virus-infected EC. 12% of mRNAs remained associated with polysomes and 0.6% were enriched ≥2-fold in polysome fractions from infected EC. Quantitative RT-PCR confirmed the microarray findings for 31 selected mRNAs. We found that enriched polysome associations of PDCD8 and JunB mRNA resulted in increased protein expression in PV-infected EC. The presence of IRES in the 5’UTR of PDCD8 mRNA, but not of JunB mRNA, was confirmed by dicistronic analysis. CONCLUSIONS: We show that microarray profiling of polyribosomal mRNA transcripts from PV-infected EC successfully identifies mRNAs whose translation is preserved in the face of stress-induced, near complete cessation of cap-dependent initiation. Nevertheless, internal ribosome entry is not the only mechanism responsible for this privileged translation.